The effect of financial transparency on aid diversion - Jan Žalman (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Aid diversion poses a significant challenge to aid-recipient countries by depleting vital resources and hindering sustainable development. In many developing nations, high levels of corruption raise concerns about whether aid funds reach their intended destination. This paper studies the impact of financial transparency on aid diversion by focusing on global efforts to reduce secrecy in tax havens since 2009. We explore how the global push to end bank secrecy has affected aid capture, finding a significant reduction in aid diversion, particularly after 2008. This reduction aligns with the initial release of customer information from tax havens, highlighting the effectiveness of the transparency measures. Our results have important implications for foreign aid allocation strategies, especially in countries involved in offshore leaks and with high corruption levels, highlighting the need for continued efforts to enhance financial transparency.
Keywords: F35; O19; 330; aid capture; offshore bank deposits; foreign aid; financial transparency; tax